Determinants of Musculoskeletal Disorders in Bamboo Woven Craftsmen in Lamongan, East Java - Putri Fortuna Salsabila; Sumardiyono; Bhisma Murti (Masters Program in Public Health, 2024)
Backround: Musculoskeletal Disorders (MSDs) are significant debilitating conditions and refer to a variety of degenerative or inflammatory conditions affecting the joints, muscles, ligaments, cartilage, and blood vessels. This research aims to determine the influence of Musculoskeletal Disorders on bamboo woven craftsmen in Lamongan. Subject and Method: This cross-sectional research was conducted in Payaman village, Solokuro District, Lamingan Regency, East Java in October-November. A total of 200 bamboo woven craftsmen were randomly selected using a random number generator. The dependent variable in this study is Musculoskeletal Disorders (MSDs). The independent variables in this study were work stress, age, length of service, duration of work, and exercise habits. The research instruments used the Nordic Body Map questionnaire, work stress questionnaire, and interviews related to age, length of service, duration of work, and exercise habits. The data analysis method uses multiple linear regression analysis. Results: Wicker craftsmen who had high job stress had an average Musculoskeletal Disorders score 0.19 units higher than those with low job stress (b = 0.19, 95% CI = -3.79 to 4.17, p=0.925). Wicker craftsmen aged 40 years and over on average had a Musculoskeletal Disorders score 9.44 units higher than those aged less than 40 years (b = 9.44, 95% CI = 4.70 to 14.18, p<0.001). Wicker craftsmen who have worked for 5 years or more on average have a Musculoskeletal Disorders score 3.34 units higher than those who have worked for less than 5 years (b = 3.34, 95% CI = -2.77 to 9.44, p=0.282). Wicker craftsmen who have a work duration of 5 hours/day and above on average have a Musculoskeletal Disorders score 7.12 units higher than those with a work duration of less than 5 hours/day (b = 7.12, 95% CI = 3.09 to 11.15, p=0.001). Conclusion: Age ≥40 years, work duration ≥5 hours, high work stress and work period ≥5 years increase the risk of MSDs in bamboo woven craftsmen. The habit of exercising ≥30 minutes/day reduces the risk of MSDs in bamboo weaving craftsmen.   Keyword: Musculoskeletal Disorder, Work Duration, Years of Work, Age, exercise habits, woven craftsmen